Foreign Direct Investment in Latin America and the Caribbean 2005 - United Nations (United Nations, 2005)
This publication sets out and analyses the main foreign direct investment (FDI) trends in the countries of Latin America and the Caribbean. Abstract In 2005 amounted to over US 68 billion, almost 11% more than in 2004. These inflows greatly exceed the figures recorded between 2001 and 2003, but they still fall short of the volumes observed during the FDI boom of the late 1990s. The region also continues to see its share in world flows decline, which suggests that it has yet to realize its true potential for attracting such investment.